EVALUATION OF THE ADAPTIVE PROPERTIES OF SPRING BARLEY VARIETIES ACCORDING TO THEIR YIELD CAPACITY IN THE ENVIRONMENTS OF THE NEAR-IRTYSH AREA IN OMSK PROVINCE - P. N. Nikolaev; P. V. Popolzukhin; N. I. Anisimov; O. A. Yusova; I. V. Safonova (Труды по прикладной ботанике, генетике и селекции, 2018)
Background. In Omsk Province there is an alternation of dry, medium moisture and wet years (respectively 40%, 30% and 20%).  This indicates the need to use barley varieties with a complex of  economically valuable traits and properties that ensure their high  yields in a wide range of varying environmental conditions.Objects of the research were 9 varieties of spring barley developed by the Siberian Research Institute of Agriculture, Russian Academy  of Agricultural Sciences, recommended for cultivation in this region.Materials and methods. The experimental part of the work was  carried out during 2011-2017, on the experimental fields of the  Siberian Research Institute of Agriculture, RAAS, located in the  southern forest-steppe in the vicinity of Omsk. The plot area was 10  m2, with 4 repetitions. The sowing rate was 4 million live grains per  1 hectare. Agricultural practice used for the experiments is generally  accepted in the West Siberian region. Mathematical processing was  carried out by the method of the analysis of variance; yield  adaptability, stability and plasticity parameters were calculated.Results. The average yield of the studied barley varieties in the  environments of Omsk's Near-Irtysh area was 3.90 t/ha - it was the  mean value for the period of studies. The barley yield varied greatly  depending on environmental conditions and hereditary  characteristics of varieties, which was confirmed by the results of the variance analysis: the share of the influence of the "year of testing"  factor on the yield was 77.5%. The best conditions for the formation  of increased yields during the period of research were observed: in 2011 and 2015 (5.28 and 5.78 t/ha), with a maximum index of  environmental conditions (Ij = 1.38 and 1.88, respectively).  Unfavorable conditions were noted from 2012 to 2014: yields  decreased to 2.33 4 3.54 t/ha, with Ij = -0.36 4 -1.57. All studied  varieties exceeded the reference 'Omskiy 91' by 7.0 4 39.3%. The most adaptive among barley varieties as far as their yield is  concerned in the conditions of Omsk's Near-Irtysh region were the  varieties: 'Podarok Sibiri', 'Omskiy 99', 'Omskiy 100' and 'Omskiy  95'. The sum of the ranks of the above varieties according to their  general and specific adaptive abilities, breeding value of the  genotype, regression coefficient, stability variance, stability index. and steadiness of the stability index was 20-30.Conclusion.  Varieties 'Podarok Sibiri', 'Omskiy 99', 'Omskiy 100' and 'Omskiy 95'  are highly adaptable and can provide high stable yields in a wide  range of variation in the natural environments of the Near-Irtysh area in Omsk Province.